Performance of an Integrated Treatment System Combining Ozonation and GAC‐Enhanced Sand Filtration for Drinking Water Treatment. Issue 11 (26th October 2015) - Baig, Shams Ali; Sheng, Tiantian; Zhu, Jianwen; Xu, Xinhua
Abstract : This study is related to the removal of organics and other pollutants from drinking water using an integrated treatment system consisting of coagulation–sedimentation, ozonation and granular activated carbon (GAC)‐enhanced sand filtration. Standard methods and instruments were employed to measure turbidity, chemical oxygen demand determined by using the permanganate method as permanganate index (CODMn ), UV254, total organic carbon (TOC), ammonia and nitrite of raw and treated water under controlled laboratorial conditions. The experimental results demonstrated that the total removal rates of turbidity, CODMn, UV254 and TOC were in the range of 98–99.9, 21–71, 33–73 and 20–47%, respectively, in different units of the integrated treatment system. GAC‐enhanced sand filtration significantly removed ammonia and nitrite, and the average removal efficiency was attained to 88 and 98%, respectively. In addition, most of the organic matter concentrations were observed to be reduced in GAC‐enhanced sand filtration and only small molecular weight compounds were detected in the effluent. All these pollutant reductions were noticed in the upper 350 mm of the activated carbon column in GAC‐enhanced sand filtration. The findings from this study suggest that the integrated treatment process can efficiently remove organics and other toxic pollutants from drinking water and can be a better alternative to conventional treatment. Abstract : An integrated treatment system was designed for drinking water treatment. The main processes include sedimentation, ozonation and GAC‐enhanced sand filtration. An average removal of 99, 88 and 98% for turbidity, ammonia and nitrite was achieved. Moreover, the ozonation process reduced the higher MW organics into smaller MW organic compounds.